2005
DOI: 10.1111/j.1365-2524.2005.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Social support in the healthcare setting: the role of volunteers

Abstract: The participation of volunteers in the National Health Service (NHS) has been actively promoted during recent years, particularly within community and primary healthcare services (National Health Service 1996, 1998). As a consequence, volunteers currently make a significant contribution to health and social care within the UK. Concerning this contribution, the literature often portrays the volunteers' role as one of providing social support. In the present paper, the authors attempt to explore this role in mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…Faulkner & Davies [18] outlined four types of social support: instrumental support, involving the provision of tangible resources to alleviate difficulties; appraisal support, which helps individuals to evaluate the impact of situations; informational support, which provides individuals with information to deal with problems; and emotional support, which enhances self-esteem and encouragement. In this study, the nurse case managers provided all four types of support, and the volunteers backed up by the social workers provided informational and emotional support [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faulkner & Davies [18] outlined four types of social support: instrumental support, involving the provision of tangible resources to alleviate difficulties; appraisal support, which helps individuals to evaluate the impact of situations; informational support, which provides individuals with information to deal with problems; and emotional support, which enhances self-esteem and encouragement. In this study, the nurse case managers provided all four types of support, and the volunteers backed up by the social workers provided informational and emotional support [6].…”
Section: Discussionmentioning
confidence: 99%
“…The research team has used the Omaha System in the local community and found it comprehensive and valid for use in the local context [6]. In supporting the NCM, the TVs would provide social support to the patient mainly in the emotional dimensions by expressing concerns and showing support [18]. The TVs had a resource kit on healthy home environment and available community resources if they need to provide some relevant information to the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts are needed to build education and information networks based on these sources. Health care professionals and social service agencies can reach a large number of community-dwelling adults and disseminate information that enables them to deal with their problems and to improve their perceptions about aging in place and moving, including whether, where, and when to seek help or move (Faulkner and Davies 2005;Schiamberg and McKinney 2003). These information sources can provide informational support in the decision-making or problemsolving process, promoting public awareness of community-based resources for coping with age-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…2010), relatively little attention has been directed to developing interventions to address the needs of different types of caregivers in hospice palliative care. The gap in understanding how to best support caregivers is particularly surprising given the ongoing calls for health‐promoting palliative care (Kelleahear 1999) and the burgeoning literature on the importance of social support for health‐care and social care in the community more generally (Faulkner & Davies 2005).…”
Section: Introductionmentioning
confidence: 99%